2002
DOI: 10.1177/15248380020033005
|View full text |Cite
|
Sign up to set email alerts
|

Inmate-to-Inmate Prison Sexuality

Abstract: For the past 90 years, sociologists, psychologists, and penologists have been studying inmate-to-inmate prison sexuality. These researchers have made great strides in advancing the study of prison sexuality. Although many may consider the issue to be deviant, prison sex researchers have made positive contributions to the study of one of the most controversial issues in corrections. In this review, the authors seek to provide readers with an understanding of not only what researchers have uncovered about inmate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Here the justice is likely referring to issues outside of the prison system. However, when coupled with the high cost of some punishments, such as segregation, and research indicating that consensual sexual activity may not contribute to a violent prison culture as much as other activities that are punished less (see Borchert, 2016;Hensley & Tewksbury, 2002), DOCs should reconsider whether consensual sexual behaviors should be covered under the same policy and punishments as coerced behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here the justice is likely referring to issues outside of the prison system. However, when coupled with the high cost of some punishments, such as segregation, and research indicating that consensual sexual activity may not contribute to a violent prison culture as much as other activities that are punished less (see Borchert, 2016;Hensley & Tewksbury, 2002), DOCs should reconsider whether consensual sexual behaviors should be covered under the same policy and punishments as coerced behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that the "preponderance of the activity is consensual sex rather than rape" (p. 427). Similarly, Hensley and Tewksbury (2002) found that fear of rape is much higher than the actual occurrences of sexual assault.…”
Section: Consensual Sex Among Inmates In Prisonsmentioning
confidence: 97%
See 2 more Smart Citations
“…These results seem to reflect the difficulty in studying consensual sexuality in prison rather than the reality. In fact, methodological and conceptual variables (Hensley and Tewksbury 2002), along with individual differences in the inmate population might explain such disparities (Hensley, Koscheski and Tewksbury 2005). Furthermore, it is not always easy to distinguish consensual and forced sexual contacts, specifically when covert strategies of coercion are used (Eigenberg 2000a).…”
Section: Literature Reviewmentioning
confidence: 99%